Online Engagement Factors on Instagram Local Fashion Brand Accounts - Raidah Rachmah , Rima; Mayangsari, Lidia (KnE Social Sciences, 2020)
Instagram is one of the most popular social media among young people. Indeed, Instagram not only used as social media but also a marketing tool for local fashion brands. There are various phenomena of Instagram marketing, yet there is still a lack of explanation of why the phenomena happened. Therefore, to propose an active social media marketing in Instagram for local fashion brands, identification of consumer engagement in social media is necessary. The objective of this research is to identify the forms of communication in which consumers most enthusiastically interact with local fashion brands on Instagram and explore the correlation between Instagram contents of fashion brands with the engagement of the consumers. The researcher surveyed through an online questionnaire as a tool to collect the data with Instagram active users as the requirement for respondents. The researcher found out that the content type of post characteristics influences boosting customer engagement. In this research, the content type classified into entertainment, informative, and remuneration posts. Each content type has different results in controlling customer engagement. Among the three classifications of content types, entertainment content type has the most substantial influence on customer engagement. Therefore, local fashion brands are recommended to utilize their marketing strategy by creating more entertainment content type, among other types on Instagram. Keywords: Instagram, social media marketing, content type, customer engagement.